"Save our students": contesting discourses of racist attacks against Indians down under. Issue 1 (2nd January 2016) - Das, Purba
Abstract : This paper seeks to understand the dominant civic discourses of accusation of racism leveled against the Australians as expressed by the victims of racist attacks and Indian Government officials in the Times of India and Outlook India news magazines. The aim of the paper is to understand how the logics of the discourses have constituted the racially motivated attacks on the Indian diaspora in Australia, and how the nationalistic sentiments are fostered among the diasporic Indians and the Indians in India. The paper argues that there is a mutual production of diasporic and homeland nationalism in the face of a crisis that hits the Indian diaspora in Australia. This analysis also brings to fore the ideology of multiculturalism in Australia.